Wild boars from Sweden, Austria, the Czech Republic and Japan possess intact mannose‐binding lectin 2 (MBL2) genes. (25th March 2015) - Bergman, I. M.; Okumura, N.; Uenishi, H.; Hammer, S. E.; Knoll, A.; Edfors, I.; Juul‐Madsen, H. R.
Summary The two‐nucleotide deletion recently detected in the mannose‐binding lectin 2 gene in purebred and crossbred domestic pigs was not found among 68 wild boars representing 4 populations from Europe and Asia. This suggests that the deletion is a result of breeding and/or genetic drift/bottle necks.